2016
DOI: 10.1038/srep19162
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation is critical for tooth agenesis: implications for sporadic non-syndromic anodontia and hypodontia

Abstract: Hypodontia is caused by interactions among genetic, epigenetic, and environmental factors during tooth development, but the actual mechanism is unknown. DNA methylation now appears to play a significant role in abnormal developments, flawed phenotypes, and acquired diseases. Methylated DNA immunoprecipitation (MeDIP) has been developed as a new method of scanning large-scale DNA-methylation profiles within particular regions or in the entire genome. Here, we performed a genome-wide scan of paired DNA samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Mir‐143 and mir‐145 have been proven to regulate odontoblastic differentiation in a posttranscriptional manner . DNA methylation and histone modification have also been reported to have some effects in tooth‐related cells . Recent study indicated a potential role of DNA methylation in odontoblastic differentiation of hDPCs as knockdown of TET1 would suppress odontoblastic differentiation through attenuated hydroxymethylation and transcription of FAM20C.…”
Section: Discussionmentioning
confidence: 99%
“…Mir‐143 and mir‐145 have been proven to regulate odontoblastic differentiation in a posttranscriptional manner . DNA methylation and histone modification have also been reported to have some effects in tooth‐related cells . Recent study indicated a potential role of DNA methylation in odontoblastic differentiation of hDPCs as knockdown of TET1 would suppress odontoblastic differentiation through attenuated hydroxymethylation and transcription of FAM20C.…”
Section: Discussionmentioning
confidence: 99%
“…Our study results confirm previous findings indicating that tooth agenesis depends on variability of the ethnic population. We also stipulated that NSTA phenotypic variability in the case of the same disease‐causing mutation could be explained by the presence of polymorphisms or epigenetic alterations . Therefore, we hypothesize that a specific tooth‐agenesis phenotype could be the result of a specific combination of mutation(s) and/or polymorphism(s) in one or several genes involved in the early stages of tooth development.…”
Section: Discussionmentioning
confidence: 99%
“…The 9 genes with highest differences in methylation status have undergone further research including NFκBIB, PRKCD, Hey1 CACNA1A. All these genes are related to cell signalling pathways important during tissue and organ development …”
Section: Conclusion and Theoriesmentioning
confidence: 99%